Enhancing Broiler Chicken Performance, Gut Microbiota, and Carcass Traits through Prebiotics (Mannan-oligosaccharides) and Probiotics (Saccharomyces cerevisiae) - Hossain, Md. Imran; Hossain, Dr. Md. Mufazzal; Akhter, Sharmin (Indian Journal of Animal Nutrition, 2024)
This study was conducted to investigate the effects of prebiotics (MOS) and probiotics (yeast) on the performance, caecal microbiota, and carcass traits of broiler chicken as an alternative to antibiotics. Accordingly, 300-day-old Cobb-500 broiler chicks were randomly assigned to five treatment groups, with three replicates, each containing 20 chicks. Dietary treatments were formulated as follows: (i) control; (ii) antibiotic (0.25 g/kg feed); (iii) MOS (0.5 g/kg feed) + yeast (1.5 g/kg); (iv) MOS (1 g/kg feed) + yeast (2 g/kg); (v) MOS (1.5 g/kg feed) + yeast (2.5 g/kg). Results showed that body weight gain, feed intake, and feed conversion ratio were significantly influenced (P < 0.05) by MOS and yeast in all the treatment groups compared to the antibiotics and control. Similarly, supplementation with MOS and yeast showed a positive effect (P < 0.05) on the breast, thigh, wing, back, and gizzard weight but did not significantly (P > 0.05) affect the liver weight. All treatments were found to have significantly lower (P < 0.05) E. coli and Salmonella populations than the control. Thus, it may be concluded that MOS (1 g/kg feed) and yeast (2 g/kg feed) may be incorporated into broiler diets for better performance as an alternative to antibiotics.